Advanced programming handbook - Galanter, Eugene (New York, N.Y. : Perigee Books, 1984)
A guide to preparing for advanced computer studies in BASIC and in program structuring, as well as in machine language. Includes self tests to measure knowledge at the beginning, middle, and end of the book.
Includes index.
Bibliography: p. 215.
Keywords: Microcomputers -- Programming; BASIC (Computer program language); Structured programming; Microcomputers -- Programming; Programming (Computers); BASIC (Computer program language); Structured programming